Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/2164371
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific or Conventional Instrumentations: A Meta-analysis of Randomized Controlled Trials

Abstract: Objective. To conduct a meta-analysis of randomized controlled trials (RCTs) to compare knee arthroplasty with patient-specific instrumentation (PSI) with the conventional instrumentation (CI). Methods. RCTs were selected in PubMed and Embase from 2012 to 2018. Key data extracted included malalignment of mechanical axis, blood loss, surgical time, Oxford Knee Score (OKS), Knee Society Score (KSS), length of stay, and complications. Subgroup analysis was also performed regarding different PSI systems and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 43 publications
2
20
1
Order By: Relevance
“…High-quality comparative studies on different PSI models are needed to highlight the different technological aspects of each PSI model and their impact on radiological and clinical results. PSI is assumed to be associated with decreased blood loss, which eliminates the need to open the femoral intramedullary canal 52,48 . Thienpont et al conducted a study that included 75 PSI-TKA patients, to determine if there was any influence of PSI on blood loss.…”
Section: Clinical Results Of Computer-assisted Knee Prosthesis Surgermentioning
confidence: 99%
See 1 more Smart Citation
“…High-quality comparative studies on different PSI models are needed to highlight the different technological aspects of each PSI model and their impact on radiological and clinical results. PSI is assumed to be associated with decreased blood loss, which eliminates the need to open the femoral intramedullary canal 52,48 . Thienpont et al conducted a study that included 75 PSI-TKA patients, to determine if there was any influence of PSI on blood loss.…”
Section: Clinical Results Of Computer-assisted Knee Prosthesis Surgermentioning
confidence: 99%
“…In addition, comparable clinical and radiological outcomes with CAS systems were reported in the literature on conventional TKA. Recent high-quality studies comparing conventional TKA and CAS-TKA have reported many controversies regarding which technique yields better clinical and radiological results [47][48][49][50] . However, the CAS-TKA has already provided outcomes equivalent to those of experienced surgeons using traditional TKA, with the potential for improvements with further technological advances 51 .…”
Section: Clinical Results Of Computer-assisted Knee Prosthesis Surgermentioning
confidence: 99%
“…The application of computer-assisted techniques in TKA is growing as the importance of bone cut precision in gap-balancing has been increasingly recognized [ 32 ]. When a surgeon uses measured resection technique to perform TKA with the assistance of image-based navigation, PSI or robotics, the determination of femoral component rotation plan is relied on the identification of sTEA on the basis of preoperative imaging data (CT or Magnetic Resonance Imaging) [ 25 28 ]. However, previous studies on reproducibility of sTEA were carried out on cadaveric knees or patients’ knees during TKA [ 18 20 , 22 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve better femoral component rotation and flexion gap, more precise measurement is needed to locate femoral rotation axis based on sTEA methodology. With wider application of navigation, patient-specific instrumentation (PSI), robotics or other computer-assisted surgical techniques [ 25 28 ], sTEA could be identified by surgeons or engineers during preoperative planning with assistance of three-dimensional (3D) images. Intraoperative femoral rotation osteotomy could be guided by robot, PSI or navigation after identification of sTEA preoperatively or intraoperatively [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…While these are estimated to be generally around 10% [ 116 ], even higher rates have been reported in the literature depending on the collective, surgical time, and surgical site [ 117 , 118 ], with the highest rates reported for pelvic implants, with infection rates of up to 42% [ 118 ]. For both complications, new design concepts offer a much better perspective for future patients treated with such implants: Patient-specific instrumentation and patient-specific implants can shorten the surgical time required for these procedures [ 119 , 120 , 121 ], thus also possibly reducing the risk of perioperative infection [ 118 ]. They also allow us to mechanically better address even complex defects than do prefabricated solutions, thus possibly also leading to better long-term survival.…”
Section: Current Trends and Future Perspectivesmentioning
confidence: 99%